½M Coffee: A Saudi Specialty Coffee Phenomenon - Kurniawan Arif Maspul; Syamsu Hidayat (Indonesian Journal Publisher, 2026)
This study examines ½M Coffee as a distinctive phenomenon at the intersection of Saudi Arabia's Vision 2030 transformation, geopolitical consumer activism, and the evolution of cultural diplomacy. While existing literature addresses specialty coffee markets or soft power separately, this research reveals how a single domestic brand has become an unexpected vehicle for national identity renegotiation, quiet resistance, and global image-making. Through qualitative case study methodology and systematic document analysis—including industry reports, UNESCO inscriptions, FAO technical documents, and regional media—this investigation traces ½M's trajectory from local start-up to transnational symbol. The findings demonstrate three novel contributions: First, ½M's success is not merely commercial but fundamentally political, capitalising on boycott dynamics following the Gaza war to position itself as an ethical alternative to Western chains. Second, the brand exemplifies what this study terms